2010
DOI: 10.1186/1471-2202-11-112
|View full text |Cite
|
Sign up to set email alerts
|

Non-dominant hand movement facilitates the frontal N30 somatosensory evoked potential

Abstract: BackgroundPrevious literature has shown that the frontal N30 is increased during movement of the hand contralateral to median nerve stimulation. This finding was a result of non-dominant left hand movement in right-handed participants. It is unclear however if the effect depends upon non-dominant hand movement or if this is a generalized phenomenon across the upper-limbs. This study tests the effect of dominant and non-dominant hand movement upon contralateral frontal and parietal somatosensory evoked potentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 81 publications
0
18
2
Order By: Relevance
“…In contrast, previous research has also shown that N30 peaks are enhanced during the execution of contralateral repetitive finger-to-thumb opposition movements [15] and during self-paced gripping [8]. Furthermore, it was revealed that the facilitation of the N30 peaks occur predominantly during contralateral non-dominant rather than dominant limb self-paced gripping [7]. It was hypothesized that these facilitatory effects on N30 peaks during non-dominant hand movements resulted from increased activity in supplementary motor area (SMA), primary motor cortex (M1) and basal ganglia (BG) [7].…”
Section: Introductioncontrasting
confidence: 49%
See 3 more Smart Citations
“…In contrast, previous research has also shown that N30 peaks are enhanced during the execution of contralateral repetitive finger-to-thumb opposition movements [15] and during self-paced gripping [8]. Furthermore, it was revealed that the facilitation of the N30 peaks occur predominantly during contralateral non-dominant rather than dominant limb self-paced gripping [7]. It was hypothesized that these facilitatory effects on N30 peaks during non-dominant hand movements resulted from increased activity in supplementary motor area (SMA), primary motor cortex (M1) and basal ganglia (BG) [7].…”
Section: Introductioncontrasting
confidence: 49%
“…Importantly, abnormal sensory gating has been N30 is gated during preparation, execution or imagination of movements to the same limb as MN stimulation (i.e. ipsilateral movements) [3][4][5][6][7][8][9][10][11][12][13][14]. In contrast, previous research has also shown that N30 peaks are enhanced during the execution of contralateral repetitive finger-to-thumb opposition movements [15] and during self-paced gripping [8].…”
Section: Introductionmentioning
confidence: 76%
See 2 more Smart Citations
“…Due to the potential confound of hand dominance 4 on brain electrical activity (see Legon, Dionne, Meehan, & Staines, 2010), only right-handed 5 participants were recruited. Furthermore, participants were questioned regarding their 6 auditory and visual faculties.…”
Section: Introductionmentioning
confidence: 99%